A Web-Based Employee Management System for Keymans Malaysia Sdn Bhd - Sasikumar, Surendran; Marjudi, Suziyanti (Applied Information Technology And Computer Science, 2022)
Keymans Malaysia is still using manual method to record their employee`s data The problem faced by the organization with their existing process is data related to the employees and organization are kept in files. Next, recording and storing information such as leave requests, attendance and report are done manually by using papers and an Excel spreadsheet. The objective of this project is to design a web-based employee management system using a structured approach. This web-based system is developed by using PHP language, Xampp and MySQL for the database. The methodology used in developing this web system is the prototyping model. In conclusion, this web-based system will help Keymans Malaysia company to better manage their employee`s record with the efficient use of the database.